Performance of Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry for Identification of Scedosporium, Acremonium-Like, Scopulariopsis, and Microascus Species - Wei, Linwei; Shao, Jin; Song, Yinggai; Wan, Zhe; Yao, Limin; Wang, Hong; Yu, Jin (Frontiers in Microbiology, 2022)
Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) has emerged as a powerful microorganism identification tool. Research on MALDI-TOF MS identification of rare filamentous fungi is still lacking. This study aimed to evaluate the performance of MALDI-TOF MS in the identification of Scedosporium, Acremonium-like, Scopulariopsis and Microascus species. Sabouraud broth cultivation and formic acid/acetonitrile protein extraction were used for MALDI-TOF MS identification by a Bruker Biotyper system. An in-house database containing 29 isolates of Scedosporium, Acremonium-like, Scopulariopsis and Microascus spp. was constructed. A total of 52 clinical isolates were identified using the Bruker Filamentous Fungi Library v1.0 (FFL v1.0) alone, and Filamentous Fungi Library v1.0 plus the in-house library, respectively. The mass spectrum profile (MSP) dendrograms of the 28 Scedosporium isolates, 26 Acremonium-like isolates and 27 Scopulariopsis and Microascus isolates were constructed by MALDI Biotyper OC 4.0 software, respectively. The correct species identification rate significantly improved when using the combined databases compared with that when using FFL v1.0 alone (Scedosporium spp., 75% versus 0%; Acremonium-like spp., 100% versus 0%; Scopulariopsis and Microascus spp., 100% versus 62.5%). The MSP dendrograms differentiated Acremonium-like species, Scopulariopsis and Microascus species clearly, but cannot distinguish species in the Scedosporium apiospermum complex. In conclusion, with an expanded database, MALDI-TOF MS is an effective tool for the identification of Scedosporium, Acremonium-like, Scopulariopsis and Microascus species.